The international movie industry - Kindem, Gorham Anders (Southern Illinois University Press, 2000)
A comprehensive history of the international movie industry during the 20th century. Essays examine the film industries of 19 countries focusing on individual national movie industries' economic, social, aesthetic, technological and political/ideological development within an international context.
Keywords: Motion picture industry -- History.; Motion picture industry -- Economic aspects.; Motion picture industry -- Social aspects.; Cinéma -- Industrie -- Histoire.; Cinéma -- Industrie -- Aspect économique.; Cinéma -- Industrie -- Aspect social.; BUSINESS & ECONOMICS -- Industries -- Media & Communications.; TECHNOLOGY & ENGINEERING -- Telecommunications.; Motion picture industry; Motion picture industry -- Economic aspects; Motion picture industry -- Social aspects; Filmwirtschaft; Internationaler Vergleich; Filmindustrie.; Economische aspecten.; Sociale aspecten.; History